CHRONIC URTICARIA - Sachdeva, Sandeep (Medknow Publications & Media Pvt Ltd, 2011)
Chronic urticaria (CU) is a disturbing allergic condition of the skin. Although frequently benign, it may sometimes be a red flag sign of a serious internal disease. A multitude of etiologies have been implicated in the causation of CU, including physical, infective, vasculitic, psychological and idiopathic. An autoimmune basis of most of the ‘idiopathic’ forms is now hypothesized. Histamine released from mast cells is the major effector in pathogenesis and it is clinically characterized by wheals that have a tendency to recur. Laboratory investigations aimed at a specific etiology are not always conclusive, though may be suggestive of an underlying condition. A clinical search for associated systemic disease is strongly advocated under appropriate circumstances. The mainstay of treatment remains H1 antihistaminics. These may be combined with complementary pharmacopeia in the form of H2 blockers, doxepin, nifedipine and leukotriene inhibitors. More radical therapy in the form of immunoglobulins, plasmapheresis and cyclophosphamide may be required for recalcitrant cases. Autologous transfusion and alternative remedies like acupuncture have prospects for future. A stepwise management results in favorable outcomes. An update on CU based on our experience with patients at a tertiary care centre is presented.